Salicylic Acid Acts Antagonistically to Plastid Retrograde Signaling by Promoting the Accumulation of Photosynthesis-associated Proteins in Arabidopsis. (19th August 2021) - Hirosawa, Yoshihiro; Tada, Akari; Matsuura, Takakazu; Mori, Izumi C; Ogura, Yoshitoshi; Hayashi, Tetsuya; Uehara, Susumu; Ito-Inaba, Yasuko; Inaba, Takehito
Abstract: Plastids are involved in phytohormone metabolism as well as photosynthesis. However, the mechanism by which plastid retrograde signals and phytohormones cooperatively regulate plastid biogenesis remains elusive. Here, we investigated the effects of an inhibitor and a mutation that generate biogenic plastid signals on phytohormones and vice versa. Inhibition of plastid biogenesis by norflurazon (NF) treatment and the plastid protein import2 ( ppi2 ) mutation caused a decrease in salicylic acid (SA) and jasmonic acid (JA). This effect can be attributed in part to the altered expression of genes involved in the biosynthesis and the metabolism of SA and JA. However, SA-dependent induction of the PATHOGENESIS-RELATED1 gene was virtually unaffected in NF-treated plants and the ppi2 mutant. Instead, the level of chlorophyll in these plants was partially restored by the exogenous application of SA. Consistent with this observation, the levels of some photosynthesis-associated proteins increased in the ppi2 and NF-treated plants in response to SA treatment. This regulation in true leaves seems to occur at the posttranscriptional level since SA treatment did not induce the expression of photosynthesis-associated genes. In salicylic acid induction deficient 2 and lesions simulating disease resistance 1 mutants, endogenous SA regulates the accumulation of photosynthesis-associated proteins through transcriptional and posttranscriptional mechanisms. These data indicate that SA acts antagonistically to the inhibition of plastid biogenesis by promoting the accumulation of photosynthesis-associated proteins in Arabidopsis, suggesting a possible link between SA and biogenic plastid signaling.